EFFECT OF QUALITY COST ON PROFITABILITY OF LISTED HEALTHCARE MANUFACTURING FIRMS IN NIGERIA - Mustapha , Lateef Olumide; Onumoh, Yahaya Ahmed; Aliyu , Abdulrazak Mohammed; Dauda , Jimkuta Daniel (International Journal of Accounting & Finance Review, 2025)
The achievement of operational efficiency and profitability in manufacturing firms depends on proper quality cost management techniques. Quality costs made of prevention costs together with appraisal costs and internal failure costs determine financial performance in organizations. The financial consequences of quality cost elements remain unclear because studies about these elements are rare in the Nigerian healthcare manufacturing industry. Several researchers disagree about how much quality cost management affects profitability, which demonstrates the necessity for additional investigations in this field. The research examines how quality costs affect profitability across the Nigerian healthcare manufacturing companies that are listed on the Nigeria Exchange Group from 2012 to 2021. A correlational research approach served the study through the examination of the entire population, which consisted of all healthcare manufacturing firms listed in Nigeria. The researcher utilized stratified sampling to obtain secondary data from audited annual financial reports published on the Nigerian Exchange Group (NGX) website. STATA Version 13 software conducts multiple regression analysis that depends on panel data. Prevention cost demonstrates a positive relationship to profitability while being statistically significant according to the research results, therefore highlighting that strategic quality management investments lead to superior financial outcomes. Profitability demonstrates no significant association with appraisal cost and internal failure cost. Prevention cost emerges as the key element among all quality cost components for achieving profitability in Nigerian listed healthcare manufacturing firms. The findings presented by this research serve to strengthen knowledge about how strategic quality cost management enhances financial outcomes for Nigerian healthcare manufacturing companies. JEL Classification Codes: M11, M41, L15, L33, O55.